2017
DOI: 10.1667/rr14889.1
|View full text |Cite
|
Sign up to set email alerts
|

Factors Modifying the Radon-Related Lung Cancer Risk at Low Exposures and Exposure Rates among German Uranium Miners

Abstract: It is still not fully understood whether and how factors such as time, age and smoking modify the relationship between lung cancer and radon at low exposures and exposure rates. Improved knowledge is necessary for the dose conversion of radon in working level month (WLM) into effective dose, as currently discussed by the International Commission on Radiological Protection (ICRP). An update of the German uranium miner cohort study (n = 58,974 men) with a 10-year extension of mortality follow-up (1946-2013) was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
69
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(77 citation statements)
references
References 29 publications
6
69
2
Order By: Relevance
“…Cigarette smoke and radiation affect the cells in vitro in an additive way (Narayanan and Rao 1988;Piao and Hei 1993;Zhou et al 1999). The synergistic action, whether sub-, supramultiplicative or multiplicative, of cigarette smoking and radiation exposure was observed in epidemiological studies (Moolgavkar et al 1993;Leuraud et al 2011;Tomasek 2011;Gilbert et al 2013;Hunter et al 2015;Kreuzer et al 2018). Mauderly et al (2010) explained in their animal study the supra-additivity of cigarette smoke to alpha particle exposure in causing malignant lung cancer via delayed clearance of the alpha-emitting PuO 2 from the lungs due to particulate smoke.…”
Section: Combined Effect In In Vitro Cell Studies Versus In Animal Anmentioning
confidence: 99%
See 2 more Smart Citations
“…Cigarette smoke and radiation affect the cells in vitro in an additive way (Narayanan and Rao 1988;Piao and Hei 1993;Zhou et al 1999). The synergistic action, whether sub-, supramultiplicative or multiplicative, of cigarette smoking and radiation exposure was observed in epidemiological studies (Moolgavkar et al 1993;Leuraud et al 2011;Tomasek 2011;Gilbert et al 2013;Hunter et al 2015;Kreuzer et al 2018). Mauderly et al (2010) explained in their animal study the supra-additivity of cigarette smoke to alpha particle exposure in causing malignant lung cancer via delayed clearance of the alpha-emitting PuO 2 from the lungs due to particulate smoke.…”
Section: Combined Effect In In Vitro Cell Studies Versus In Animal Anmentioning
confidence: 99%
“…Previous studies described the following three possible ways of interaction between radiation exposure (alpha particles in epidemiological studies) and cigarette smoking: additive (Narayanan and Rao 1988;Piao and Hei 1993;Zhou et al 1999;Pierce et al 2003;Tomasek 2013), multiplicative (Pershagen et al 1994;Kreisheimer et al 2003;Jacob et al 2005;Hunter et al 2015;Kreuzer et al 2018), and supra-additive (or sub-multiplicative) (Moolgavkar et al 1993;Zhang et al 2006;Mauderly et al 2010;Leuraud et al 2011;Tomasek 2011;Meenakshi and Mohankumar 2013;Gilbert et al 2013;Hunter et al 2015;Kreuzer et al 2018). In recent years, the possibility of a supramultiplicative model has been further claimed (Kreuzer et al 2018). The influence of smoking on radio-sensitivity was also debated to vary with specific conditions, including smoking rate (Monchaux et al 1994;Liddell and Armstrong 2002;Furukawa et al 2010;Egawa et al 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kreuzer et al demonstrated a clearly increased excess risk of lung cancer at low cumulative radon exposures [45]. Moreover, it was shown that excess relative risk (ERR) for lung cancer mortality per unit of cumulative radon exposure in WLM was 0.006 (95% confidence interval (CI): 0.003; 0.010) based on 1254 lung cancer deaths [45]. According to Yarmoshenko et al the relative risk (RR) of radon-induced lung cancer mortality was 0.026 (90% CI: (0.11-0.17)) and 0.83 (90% CI: (0.52-1.12)) per radon concentration 100 Bq/m 3 for males and females, respectively [46].…”
Section: Radon Exposure and Lung Cancer: Epidemiology And Biomonitoringmentioning
confidence: 99%
“…It has been proven experimentally that an increase in the concentration of radon in living quarters for every 100 Bq/m 3 leads to an increase the risk of lung cancer to 7% annually [44]. Kreuzer et al demonstrated a clearly increased excess risk of lung cancer at low cumulative radon exposures [45]. Moreover, it was shown that excess relative risk (ERR) for lung cancer mortality per unit of cumulative radon exposure in WLM was 0.006 (95% confidence interval (CI): 0.003; 0.010) based on 1254 lung cancer deaths [45].…”
Section: Radon Exposure and Lung Cancer: Epidemiology And Biomonitoringmentioning
confidence: 99%